Differentiation of Tuberculous from Pyogenic Brain Abscesses with In Vivo Proton MR Spectroscopy and Magnetization Transfer MR Imaging - Gupta, Rakesh K.; Vatsal, Davender K.; Husain, Nuzat; Chawla, Sanjeev; Prasad, Kashi N.; Roy, Raja; Kumar, Rajesh; Jha, Deepak; Husain, Mazhar (American Journal of Neuroradiology, 2001)
BACKGROUND AND PURPOSE: MR imaging features are nonspecific with respect to the causative organism for patients with brain abscesses. On the basis of the hypothesis that the biochemical environment depends on the infecting organism and might be different in tuberculous compared with pyogenic brain abscesses, this study attempted to determine whether pyogenic brain abscesses can be differentiated from tuberculous brain abscesses by use of magnetization transfer (MT) MR imaging and in vivo proton MR spectroscopy.METHODS: Twenty-seven patients with a total of 33 pyogenic brain abscesses and three patients with a total of 12 tuberculous abscesses were evaluated with in vivo MR spectroscopy and MT MR imaging. The diagnosis in all cases was based on the culture of the causative organisms and histopathology whenever done as a part of clinical management.RESULTS: All 27 patients with pyogenic brain abscesses had lipid and lactate levels of 1.3 ppm and amino acid levels of 0.9 ppm with or without the presence of succinate, acetate, alanine, and glycine, while the three patients with tuberculous abscesses showed only such lipid and lactate levels. The MT ratio from the wall of the pyogenic abscesses was significantly higher (P < .001) than that from the tuberculous abscess wall.CONCLUSION: It might be possible to differentiate tuberculous abscesses from pyogenic abscesses by using MT MR imaging and in vivo MR spectroscopy, which could be of value in influencing the management of such cases.